Effective mosaic-based nanovaccines against avian influenza in poultry. Issue 35 (14th August 2019) - Kingstad-Bakke, Brock A.; Chandrasekar, Shaswath S.; Phanse, Yashdeep; Ross, Kathleen A.; Hatta, Masato; Suresh, M.; Kawaoka, Yoshihiro; Osorio, Jorge E.; Narasimhan, Balaji; Talaat, Adel M.
Abstract: Avian influenza virus (AIV) is an extraordinarily diverse pathogen that causes significant morbidity in domesticated poultry populations and threatens human life with looming pandemic potential. Controlling avian influenza in susceptible populations requires highly effective, economical and broadly reactive vaccines. Several AIV vaccines have proven insufficient despite their wide use, and better technologies are needed to improve their immunogenicity and broaden effectiveness. Previously, we developed a "mosaic" H5 subtype hemagglutinin (HA) AIV vaccine and demonstrated its broad protection against diverse highly pathogenic H5N1 and seasonal H1N1 virus strains in mouse and non-human primate models. There is a significant interest in developing effective and safe vaccines against AIV that cannot contribute to the emergence of new strains of the virus once circulating in poultry. Here, we report on the development of an H5 mosaic (H5M) vaccine antigen formulated with polyanhydride nanoparticles (PAN) that provide sustained release of encapsulated antigens. H5M vaccine constructs were immunogenic whether delivered by the modified virus Ankara (MVA) strain or encapsulated within PAN. Both humoral and cellular immune responses were generated in both specific-pathogen free (SPF) and commercial chicks. Importantly, chicks vaccinated by H5M constructs were protected in terms of viral shedding from divergent challenge with a low pathogenicity avian influenza (LPAI) strain at 8 weeks post-vaccination. In addition, protective levels of humoral immunity were generated against highly pathogenic avian influenza (HPAI) of the similar H5N1 and genetically dissimilar H5N2 viruses. Overall, the developed platform technologies (MVA vector and PAN encapsulation) were safe and provided high levels of sustained protection against AIV in chickens. Such approaches could be used to design more efficacious vaccines against other important poultry infections.